Strategi Pustakawan dalam Meningkatkan Minat Baca Masyarakat Majene - Muhammad Ridwan (Lentera Jurnal, 2025)
Public interest in reading in Indonesia, especially in Majene Regency, is still relatively low. Based on existing data, Indonesia ranks low in global literacy skills, which is a big challenge for librarians in increasing reading interest. This study aims to analyse the strategies implemented by librarians in Majene Regency to increase public interest in reading. The type of research used is descriptive with a qualitative approach. Primary data sources consist of library leaders, librarians, and literacy activists. Secondary data consists of articles, news, and studies relevant to this paper. The research data was collected through observation, interviews, and documentation. The data were analysed using data reduction, presentation, and conclusion-drawing techniques. This study found four strategies to increase the interest in reading in the Majene community: first, implementing the digital reading corner program (POCADI). Second, following the training and development of librarians. Third, socialisation through mobile libraries. Fourth, procurement of sustainable book collections. As a practical implication of this research, it is expected that the Majene Regional Government needs to increase attention to libraries by providing a larger budget for procuring book collections, improving facilities and infrastructure, and training librarians.